X-ray Scattering (IntechOpen, 2023)
X-ray scattering techniques are a family of nondestructive analytical techniques. Using these techniques, scientists obtain information about the crystal structure and chemical and physical properties of materials. Nowadays, different techniques are based on observing the scattered intensity of an X-ray beam hitting a sample as a function of incident and scattered angle, polarization, and wavelength. This book is intended to give overviews of the relevant X-ray scattering techniques, particularly about inelastic X-ray scattering, elastic scattering, grazing-incidence small-angle X-ray scattering, small-angle X-ray scattering, and high-resolution X-ray diffraction, and, finally, applications of X-ray spectroscopy to study different biological systems.